Intelligent Software Agents for Managing Road Speed Offences - Abbas, M.K. (Springer Verlag, 2019)
The increasing fatal road accidents because of fast driving had urged police departments to set many cameras and speed traps at some parts of the roads in an attempt to reduce the problem. Many drivers know where those cameras and speed traps are, which makes it very easy to be avoided by the drivers who intend to drive faster than the road speed limit. This research proposes a system for smart cities and/or highways to control the problem via the placement of a set of Vehicular Ad-Hoc Network (VANET) devices on the roadside and within the vehicles to achieve side to side communication. The provided communication would be responsible for delivering real time information about the car, including its speed, which would help to detect the speeding offenders. The aims of this research are to identify the factors causing the accidents to happen, warn the speeding drivers at any time about their offence and to ensure a fine will be issued for every offender. In addition, the proposed system is expected to help traffic policemen in doing their job of identifying and proving that a driver has broken the traffic rules. Â© 2019, Springer Nature Switzerland AG.